2023
DOI: 10.3390/conservation3010010
|View full text |Cite
|
Sign up to set email alerts
|

Using Botanical Gardens as Butterfly Gardens: Insights from a Pilot Project in the Gran Sasso and Monti Della Laga National Park (Italy)

Abstract: Butterfly gardens are green spaces designed as places where butterflies can feed, mate, and rest. Here, we present some perspectives on the possible use of botanical gardens in natural areas as butterfly gardens to promote insect conservation through science dissemination and citizen science activities. We explored this possibility with a project developed in the Botanical Garden of the Gran Sasso and Monti della Laga National Park (Italy). We found an extremely high butterfly richness as a result of favorable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The preference for larger and more colorful birds is also evident in zoo collections. Eight percent of the world's threatened bird species are kept in captivity [185], and zoos tend to favor birds that are not endemic or threatened [180]. Additionally, there is an indication that the average diversity of bird species in zoos declined between 1960 and 2018 [200].…”
Section: How Important Are Zoos and Botanical Gardens For Endemics An...mentioning
confidence: 99%
“…The preference for larger and more colorful birds is also evident in zoo collections. Eight percent of the world's threatened bird species are kept in captivity [185], and zoos tend to favor birds that are not endemic or threatened [180]. Additionally, there is an indication that the average diversity of bird species in zoos declined between 1960 and 2018 [200].…”
Section: How Important Are Zoos and Botanical Gardens For Endemics An...mentioning
confidence: 99%
“…Butterfly biodiversity research conducted in Pontianak City showed that there were 22 species of butterflies, indicating the city's potential as a habitat for these insects [13]. Butterfly-watching has been widely applied in various regions, but most of these activities are carried out in conservation areas and are still limited to scientific research [14][15]. The development of butterfly-watching as an urban ecotourism program is a potential new alternative to be developed to harmonize people and nature in urban areas and encourage community involvement in improving urban citizen science.…”
Section: Introductionmentioning
confidence: 99%